Improvement of Alert System against Tampering and Theft in Surveillance Cameras - Furat N. Tawfeeq (Tikrit Journal of Pure Science)
Use of Surveillance cameras in houses and markets became common, that resulted to minimize theft and make it a difficult task because it let recording and viewing what is going around. The wide application of these cameras, pushed thieves to seek new ways for abolition of the surveillance system and digital recording of events, such as cutting the signal wire between the camera and Digital video recorder or changing the direction of the camera away from the focus spot or damaging the camera or steal the device which means the loss of the recorded media. This paper focuses on such abolitions and fixed it by suggesting a way to notify the administrator immediately and automatically by Email about any violation of the system using MATLAB, which allow fast action by the administrator to fix such tampering. The results show that selecting of threshold equal to two was fair in detecting motion and value of five, in case of changing the camera direction through testing of fast and slow motions.